2012
DOI: 10.1016/j.immuni.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Deactivates Classically Activated Microglia and Protects from Inflammation-Induced Neurodegeneration

Abstract: SUMMARY Inflammation-mediated neurodegeneration occurs in the acute and the chronic phases of multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). Classically-activated (M1) microglia are key players mediating this process. Here we identified Galectin-1 (Gal1), an endogenous glycan-binding protein, as a pivotal regulator of M1 microglia activation, targeting the activation of p38MAPK-, CREB-, and NF-κB-dependent signaling pathways and hierarchically supressing downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
291
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(309 citation statements)
references
References 50 publications
13
291
3
2
Order By: Relevance
“…Strikingly, we did not observe neurotoxic effects at either structural or functional levels. This expands previous data from slice cultures (5,25,34), but contrasts with studies of neuron-glia cultures and in vivo, in which LPS exposure alone was neurotoxic (8,12,13,17,18,20,21). Several factors might account for these differences, including (i) insufficient NO levels to amplify inflammatory responses of glial cells and/or inhibit mitochondrial respiration in neurons (14,32); (ii) the neural subtype investigated (42); (iii) suppressive effects on microglia ("off" signals) from active neurons and astrocytes through cell membrane contacts, neurotransmitters, and cytokines (1, 4, 7); and (iv) the presence of antioxidative extracellular matrix components that protect neurons (43).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Strikingly, we did not observe neurotoxic effects at either structural or functional levels. This expands previous data from slice cultures (5,25,34), but contrasts with studies of neuron-glia cultures and in vivo, in which LPS exposure alone was neurotoxic (8,12,13,17,18,20,21). Several factors might account for these differences, including (i) insufficient NO levels to amplify inflammatory responses of glial cells and/or inhibit mitochondrial respiration in neurons (14,32); (ii) the neural subtype investigated (42); (iii) suppressive effects on microglia ("off" signals) from active neurons and astrocytes through cell membrane contacts, neurotransmitters, and cytokines (1, 4, 7); and (iv) the presence of antioxidative extracellular matrix components that protect neurons (43).…”
Section: Discussionsupporting
confidence: 81%
“…In primary monocultures and microglia-neuron cultures, LPS exposure alone or in combination with IFN-γ for a "booster" triggers the massive release of proinflammatory and cytotoxic factors, such as TNF-α, IL-6, and nitric oxide (NO), finally resulting in neuronal death (8,(11)(12)(13)(14)(15)(16)(17)(18). Similar effects were observed in vivo after intracerebral administration of LPS (19)(20)(21).…”
mentioning
confidence: 85%
“…13 Our recent studies revealed that Gal-1 induces microglia deactivation and prevents inflammation-induced neurodegeneration. 20 In the present study, we successfully uncoupled the microglial deactivating effect, which was observed using both WT and monomeric Gal-1 from the neuroregenerative effect, which was verified only when high concentrations of WT Gal-1 were used. This data suggest the importance of dimerization in the neuromodulatory functions of Gal-1.…”
Section: Discussionmentioning
confidence: 64%
“…Gal-1 interrupts Sema3A pathway after SCI HR Quintá et al full neuroregenerative effect through binding to NRP-1 but also contributes to deactivating microglia 20 and dampening pathogenic immune cells, 55 the coordinated action of these biological effects may lead to a better restorative process after medullar lesion.…”
Section: Figure 8 Continuedmentioning
confidence: 99%
See 1 more Smart Citation